EFL Students’ Perspectives on Their Self-efficacy in Speaking During Online Learning Process - Rista Ananda Ningias; Lilia Indriani (English Learning Innovation (englie), 2021)
This article illustrates the EFL students' perspectives toward self-efficacy of them in speaking during the online learning process. Self-efficacy defined as a person believes that he/she could manage the situation and get a positive outcome. It points out to the intuition in one’s capacity to execute and organize the action required in producing the given attainments. Self-efficacy is very crucial for students in studying a language, especially for the fourth language skills. To achieve the qualification of English communication, mastering the fourth integrated skills is very necessary. Speaking includes in this term. The aim of this article was to analyze the EFL students’ perspective about their self-efficacy in speaking during the online class activity. The research was conducted on 35 EFL learners of English Department Student at Tidar University. The researcher uses the descriptive quantitative method in analyzing the data. In obtaining them, the researcher employed a survey study by using a questionnaire with 20 close-ended questions. The result showed that the learners have enough self-efficacy in speaking during online learning. The high percentage of neutral option still dominate them. However, the final result of the data shows that learners have strong self-efficacy. Keywords: EFL Students, Online Learning, Speaking, Self-efficacy